Enzymatic extraction of gelatin from threadfin bream (nemipterus japonicas) skin / Normah Ismail and Izaty Hasni Ismail - Ismail, Normah; Ismail, Izaty Hasni (2016)
Threadfin bream (Nemipterus japonicus) skin gelatin was enzymatically extracted for 6 or 12 hrs at 60°C, pH 8 in the presence of alcalase. The gelatin was analyzed for yield, gel strength, melting point, setting point, setting time, viscosity, solubility and molecular weight distribution. The gelatin was also compared with commercial gelatin. The 12 hrs extraction time yield 7.74% gelatin and the gelatin was more soluble while 6 hrs gelatin resulted in 5.69% yield. Gel strength of the extracted gelatin decrease with longer extraction time. The 6 hrs gelatin exhibited gel strength of 324.93g which was very close to the commercial gelatin (342.10g) while 12 hrs gelatin gel strength was 202.47g. Melting points of threadfin bream gelatin increased when the extraction time increased ranging from 25.53 to 29.42°C while commercial gelatin melted at 34.03°C. Threadfin bream gelatins set at lower temperature and longer time with increase in extraction time compared to commercial gelatin. The gelatin extracted for 6 hrs resulted in higher gel strength, viscosity, melting point, setting point and shorter setting time than the 12 hrs gelatin. This shows that the 6 hrs extracted gelatin is more suitable to be used in food production than the 12 hrs gelatin.